Citizens’ participation in urban planning in Azerbaijan - Kistaubayeva, Aygerim; Mammadli, Sarhad; Durán, Alejandra García (ADA University, 2021)
This capstone project analyzes city inhabitant’s involvement in urban development in Azerbaijan and proposes a policy solution that tackles the lack of citizen participation in urban planning and of mechanisms involving citizens in this process. The proposal is the result of the evaluation of three policies that address the three main causes of the problem: Unprioritized collective urban development solved by implementing the community practice of Planning for Real (PFR); Absence of training and institutional structure for participatory planning with education and training of citizens to participate in urban planning as a social capital; and to solve the exclusionary urban planning and execution process it is proposed to involve citizens in urban planning by using digital tools. After evaluating the policies presented, this policy paper concludes that the most appropriate and inclusive solution for Azerbaijan is to adopt the Planning for Real (PFR) community process in urban developments.
Keywords: Public and International Affairs; Urban development; Urban planning; Citizens--Urban development